Maternal, umbilical arterial and umbilical venous 25‐hydroxyvitamin D and adipocytokine concentrations in pregnancies with and without gestational diabetes. (23rd October 2013) - McManus, Ruth; Summers, Kelly; de, Barbra; Cohen, Nicole; Thompson, Alexandra; Giroux, Isabelle
Summary Objective Gestational diabetes mellitus (GDM) has been associated with inflammation as well as Vitamin D insufficiency. While Vitamin D has anti‐inflammatory properties, relationships between Vitamin D and inflammatory markers remain unexplored in GDM. Therefore, this case‐–control study investigated adipocytokine and Vitamin D [25(OH)D] concentrations and correlations in GDM and control women, as well as their neonates. Design/Participants/Measurements seventy‐three women participated: 36 GDM and 37 controls. Maternal samples were drawn at 31 weeks. Umbilical arterial and venous samples were collected at birth. 25(OH)D and adipocytokine concentrations were compared for GDM vs control maternal, umbilical arterial and venous samples. Correlations were explored between biochemical results, maternal and neonatal demographics. Results Compared with age‐ and weight‐matched control participants, GDM women had significantly lower concentrations of 25(OH)D (77·3 ± 24·3 vs 93·2 ± 19·2 nm/l; P = 0·009); adiponectin (17·5 ± 11·8 vs 34·1 ± 20·3 μg/ml, P < 0·001); resistin (25·4 ± 9·1 vs 31·9 ± 12·1 ng/ml, P = 0·045); and plasminogen activator inhibitor‐1 (PAI‐1) 13·9 ± 10·0 vs 21·0 ± 12·6 ng/ml, P = 0·038), while delivering 1 week earlier (38·2 ± 1·2 vs 39·5 ± 0·9 weeks, P < 0·001). GDM maternal 25(OH)D concentrations positively correlated with PAI‐1, IL‐8 and TNF‐α concentrations. Umbilical 25(OH)D concentrations were not significantly different in GDM vs control offspring, whereas adiponectin, resistin and PAI‐1 concentrations were significantly lower in GDM offspring. Conclusions GDM women had lower 25(OH)D concentrations than controls, while neonatal umbilical concentrations of 25(OH)D did not differ. GDM maternal and GDM offspring had lower adiponectin, resistin and PAI‐1 concentrations compared with controls. Results suggest that both GDM women and their offspring demonstrate abnormal adipocytokine patterns.